2022
DOI: 10.1038/s41591-022-02015-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular response to tebentafusp in previously treated patients with metastatic uveal melanoma: a phase 2 trial

Abstract: In patients with previously treated metastatic uveal melanoma, the historical 1 year overall survival rate is 37% with a median overall survival of 7.8 months. We conducted a multicenter, single-arm, open-label phase 2 study of tebentafusp, a soluble T cell receptor bispecific (gp100×CD3), in 127 patients with treatment-refractory metastatic uveal melanoma (NCT02570308). The primary endpoint was the estimation of objective response rate based on RECIST (Response Evaluation Criteria in Solid Tumours) v1.1. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 51 publications
2
57
1
Order By: Relevance
“…Of note, in the phase I dose escalation study, among patients who received ICPIs following tebentafusp, there were a group who had a superior than expected response to ICPIs. 42 This may be due to upregulation of PD-1 and PD-L1; epitope spreading by tebentafusp and potentially an increased presence of TILs. ICPIs in UM may therefore possess greater efficacy if given following tebentafusp delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in the phase I dose escalation study, among patients who received ICPIs following tebentafusp, there were a group who had a superior than expected response to ICPIs. 42 This may be due to upregulation of PD-1 and PD-L1; epitope spreading by tebentafusp and potentially an increased presence of TILs. ICPIs in UM may therefore possess greater efficacy if given following tebentafusp delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, model simulations imply that efficacy is not likely to be impacted by step‐up dosing; step‐up dosing reduced tumor trimer formation <20% at 8 weeks compared with flat dosing, with tumor trimer formation between the two dose regimens becoming more similar as the number of doses increases. Given the median follow‐up duration for a phase II tebentafusp study was 19.5 months, 45 it is therefore likely that step‐up dosing would not impact tebentafusp efficacy. Indeed, clinical studies with tebentafusp and other bispecifics have found that step‐up dosing improves safety without compromising efficacy 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a T cell engager medication comprising a bispecific fusion anti-CD3 protein targeting gp100 membrane antigen (Tebentafusp) has shown potent antitumor response with significant improvement of overall survival at 1 year in patients with metastatic refractory melanoma , and HLA-A*02:01-positive uveal melanoma patients for which it gained FDA approval in 2022. We have therefore selected gp100, but also Trp1 tumor-specific antigens, for the construction of a dual LF N conjugate and assessed DCs targeting efficacy in an aggressive melanoma model.…”
Section: Discussionmentioning
confidence: 99%